(untitled) (Scientific journal of the Fergana State University, 2024)
This article studies scientific and theoretical views on spelling and its norms and gives a reaction to them. The scope of orthoepy and the problem of orthoepic norms are also discussed. This article examines the research of world and Uzbek linguists who have put forward important scientific and theoretical views on the concept of orthoepy and its features in linguistics. Their opinion, point of view and scientific theories on this matter are expressed, as well as the opinions of many researchers about the concept of spelling and its characteristics. Over time, one of the options becomes the leading one, and the rest are used less frequently and fall out of use, and the choice of one of the options as the leading one is influenced by factors such as its compliance with the objective laws of language development and its widespread use.